2021
DOI: 10.31849/elsya.v3i1.5949
|View full text |Cite
|
Sign up to set email alerts
|

Investigating EFL Students’ Perceptions on E-learning Paradigm-Shift During Covid-19 Pandemic

Abstract: The purpose of this research article is to investigate the perceptions of EFL students during the Covid-19 pandemic on implementing e-learning at university-level education in the EFL context of Afghanistan. The covid-19 pandemic has globally led the universities towards a paradigm-shift. As well as the instant development of ICT has restructured the content and the context of education particularly teaching and learning EFL. To determine the barriers and opportunities of implementing e-learning in EFL educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 11 publications
(21 reference statements)
4
32
0
1
Order By: Relevance
“…It was evident that e-learning strategies established a supportive rapport that successfully qualifies for quality indicators for the online education system. The results aligned with the study of Rahim 2021 (16) , and Fahara et al, (17) who indicated similar qualities such as time spent in the learning atmosphere, days posted (Course content) on the portal, the number of feedback made to students within a discussion, and timeliness of responses to students' questions and grading of assignments considered as a measure of quality. Students revealed verbal immediacy by calling the students by name, using humor, and encouraging students' input and discussion.…”
Section: Discussionsupporting
confidence: 86%
“…It was evident that e-learning strategies established a supportive rapport that successfully qualifies for quality indicators for the online education system. The results aligned with the study of Rahim 2021 (16) , and Fahara et al, (17) who indicated similar qualities such as time spent in the learning atmosphere, days posted (Course content) on the portal, the number of feedback made to students within a discussion, and timeliness of responses to students' questions and grading of assignments considered as a measure of quality. Students revealed verbal immediacy by calling the students by name, using humor, and encouraging students' input and discussion.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, the world has been stressful for everyone and the outbreak of the virus caused problems in education. Afghanistan as a post-conflict country is not an exception in Asia ( Rahim and Chandran, 2021 ). To avoid the spread of COVID-19, the Afghan government took certain measures.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al (2020) argued that almost all countries experienced changes in education. Since the spread of the COVID-19 pandemic, the universities have transformed teaching and learning and the lecturers have been conducting online classes (Rahim and Chandran, 2021). The Ministry of Higher Education introduced an online learning system called "Higher Education Learning Management System" (HELMS).…”
Section: Introductionmentioning
confidence: 99%
“…The use of ICT in ELT assists students in improving their attitudes toward learning English (Idowu & Gbadebo, 2017;Sabti & Chaichan, 2014). The implementation of ICT in the classroom may result in positive attitudes among both teachers and learners (Benghalem, 2015;Rahim & Chandran, 2021).…”
Section: The Benefits Of Ict For English Language Learning and Teachingmentioning
confidence: 99%